Stress in the Air: A Conjecture - Oded Stark (Institute of Labor Economics (IZA), 2024)
The 1949 study The American Soldier: Combat and Its Aftermath, Volume II, by Stouffer et al. presents detailed accounts of the attitudes of American fighter pilots toward the stress experienced by them and of the policies and practices of the American Air Force command in addressing this stress during WWII. The 2022 study "Killer incentives" by Ager et al. documents an aspect and a repercussion of the stress of German fighter pilots and can be used to identify the response to that stress by the German Air Force command during WWII. Drawing on these two studies, in this paper I construct fighter pilot stress profiles in the two air forces. The picture that emerges is that there is a stark difference between the approaches of the two commands. This diversity leads me to conjecture that the American Air Force command explicitly sought to forestall and curtail fighter pilots' stress, whereas the German Air Force command implicitly cultivated and engineered fighter pilots' stress.
Keywords: D01; D23; D9; E7; H56; I12; I38; J28; J38; J48; J58; N42; N44; 330; WWII; fighter pilots; combat missions; fighter pilot stress; policies and practices of the American Air Force in curtailing stress; policies and practices of the German Air Force in cultivating stress